2015
DOI: 10.1007/s00467-014-3041-y
|View full text |Cite
|
Sign up to set email alerts
|

Mycophenolate mofetil therapy for steroid-resistant IgA nephropathy with the nephrotic syndrome in children

Abstract: BackgroundImmunoglobulin A nephropathy (IgAN) presents as nephrotic syndrome (NS) relatively rarely, and the current treatment experience of IgAN patients with NS is mostly with adults. The objective of our study was to investigate the efficacy of corticosteroids and mycophenolate mofetil (MMF) in treating childhood immunoglobulin A nephropathy (IgAN) with nephrotic syndrome.MethodsA total of 58 children (39 boys and 19 girls) diagnosed with nephrotic syndrome and primary IgAN were enrolled in the study. All t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 41 publications
(29 reference statements)
1
12
0
Order By: Relevance
“…In particular, it was observed that the serum level of IgA, IgG, and IgG/IgM ratio in the group of patients with steroid resistance were significantly lower than those of the ones with steroid sensitivity (P < 0.05). The current study results also coincided with those of previously published authors' study (20)(21)(22)(23)(24). Biopsy was performed on 19 patients with steroid-resistant NS, and histopathological results showed that the rate of FSGS, MesPGN, and MPGN accounted for 78.9% of them.…”
Section: Steroid Resistance In Vietnamese Children With Nssupporting
confidence: 91%
“…In particular, it was observed that the serum level of IgA, IgG, and IgG/IgM ratio in the group of patients with steroid resistance were significantly lower than those of the ones with steroid sensitivity (P < 0.05). The current study results also coincided with those of previously published authors' study (20)(21)(22)(23)(24). Biopsy was performed on 19 patients with steroid-resistant NS, and histopathological results showed that the rate of FSGS, MesPGN, and MPGN accounted for 78.9% of them.…”
Section: Steroid Resistance In Vietnamese Children With Nssupporting
confidence: 91%
“…The characteristics of the included studies are summarized in the Table 1 . The inclusion criteria used in two trials [ 13 , 14 ] was IgAN patients with nephrotic syndrome, and the other one [ 15 ] was biopsy-proved IgAN and urinary protein excretion ranging from 1.0 to 3.5 g/24h. Another two studies [ 16 , 17 ] did not limit the scope of proteinuria, and the last study [ 16 ] used the immunosuppressive therapy and was only provided the data of M1, E1, S1, T0, and T1/2, without M0, E0, and S0.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies have also showed the good response to steroid in patients with minimal histopathological changes and resistant to steroid therapy with severe pathological change [ 19 – 21 ]. Kang Z et al found that patients with M1, S1, and T1/2 were resistant to steroid therapy [ 14 ], however the results have not been validated in the Oxford classification. To our knowledge, it was the first meta-analysis that found the presence of the M1, S1, or T1/2 lesions in the Oxford Classification was strongly associated with the resistance to steroid/immunosuppressive therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Another European study using an enteric formulation of budesonide also demonstrated significant renoprotective effects after 9 months of therapy For steroid‐resistant patients, MMF may be individually considered in Chinese subjects without advanced tubulointerstitial changes, but it is not recommended for Caucasians . (Not Graded) For IgAN/MCD overlap syndrome, treatment should be analogous to that of MCD (see item 1).…”
Section: Glomerulonephritidesmentioning
confidence: 99%